Economic impact of prescribing error prevention with computerized physician order entry of injectable antineoplastic drugs. (March 2013) - Nerich, V; Borg, C; Villanueva, C; Thiery-Vuillemin, A; Helias, P; Rohrlich, P-S; Demarchi, M; Pivot, X; Limat, S
A cost–benefit analysis was carried out to determine the potential economic costs and benefits of pharmaceutical analysis in preventing prescribing errors for full standardized injectable antineoplastic drugs computerized physician order entry, in a pharmaceutical unit (University teaching hospital), compared with theoretical setting with no pharmaceutical analysis. The viewpoint is that of the payer or the French national Public Health Insurance system, and is limited to hospital cost (only direct medical costs related to net cost and net benefit. A decision analysis model was performed to compare two strategies: with pharmaceutical analysis (±pharmacy intervention) and without pharmaceutical analysis. Results are expressed in terms of benefit-to-cost ratio and total benefit. The robustness of the results was assessed through a series of one-way sensitivity analyses. Over 1 year, prescribing error incidence was estimated at 1.5% [1.3–1.7], i.e. 218 avoided prescribing errors. Potential avoidance of hospital stay was estimated at 419 days or 1.9 ± 0.3 days per prescribing error. Cost–benefit analysis could estimate a net benefit-to-cost ratio of 33.3 (€17.34/€0.52) and a total benefit at €16.82 per pharmaceutical analysis or €249, 844 per year. The sensitivity analysis showed robustness of results. Our study shows a substantial economic benefit of pharmaceutical analysis and intervention in the prevention of prescribing errors. The clinical pharmacist adds both value and economic benefit, making it possible to avoid additional use of expensive antineoplastic drugs and hospitalization. Computerized physician order entry of antineoplastic drugs improves the relevance of clinical pharmacist interventions, expanding pharmaceutical analysis and also the role of the pharmacist.